Nicaragua : Integration of Natural Medicine and Complementary Therapies, Revival of Traditional Ancestral Medicine in Indigenous Peoples and Afro-descendants - Mendoza, Maria Jose; Aviles, Maritza Ruiz; Gordillo-Tobar, Amparo; Colchao, Maria; Herrera, Emilce; Rodriguez, Evelyn (World Bank, Washington, DC, 2021)
Since its inception in 2014, the Institute of Natural Medicine and Complementary Therapies (IMNTC) has set up a strategy for providing, promoting, and developing traditional and natural medicine and complementary therapies based on two key lines of action: revival of ancestral knowledge and practices of indigenous peoples and afro-descendants, and integration of IMNTC into the community and family health model (MOSAFC). Based on this and with World Bank (WB) - led technical and financial support under the Strengthening the Public Health Care System Project, the healthcare staff training plan is being implemented, along with the promotion, education, and dissemination of natural medicine, research, and the strengthening of complementary therapy and holistic pain management clinics nationwide.